Visible Light-Responsive Photocatalysts: Doping, Sensitization and Surface Modification - Ohtani, Bunsho (Recent Patents on Engineering, 2010)
Recent patents and related papers on design and preparation of visible light-responsive photocatalysts for water splitting to give hydrogen and oxygen and for mineralization of organic compounds under aerated conditions by doping, sensitization and surface modifications of conventional metal oxide crystallites and by using metal nitrides and/or their solid solutions with metal oxides are reviewed with discussion of the mechanisms of development of visible-light absorption and chemical reactions, especially of hydrogen liberation and oxygen reduction, occurring on the surface of visiblelight photocatalysts.
Keywords: standard electrode potential